Pentingnya Memahami Konsep Sejarah dalam Konteks Pendidikan Islam - Mardinal Tarigan; Suci Ati Cahya; Afdilla Zulkarnain (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Understanding the importance of education in guiding human civilization is the primary focus of various scientific studies. Islamic education, as an integral part of the global educational journey, is no exception in academic scrutiny. This journal discusses the concept of the history of Islamic education and its role in shaping worldviews and human behavior. The author highlights various perspectives on education, including from societal and individual standpoints. These perspectives affirm that education is not just about religious knowledge alone but also encompasses the development of moral, scientific, and physical aspects. The journal discusses the history and development of Islamic education over time, from classical to modern periods. Three main periods, namely classical, medieval, and modern, are elaborated with emphasis on important stages in the history of Islamic education. The research method used is a literature review approach, collecting and analyzing various related literature through electronic media. The results and discussions elaborate on the understanding of history, the concept of Islamic educational history, and the history of Islamic education development over time, including the methodology aspects used in the research. The discussion also involves analysis of the objectives of Islamic education, the objects and scope of Islamic educational history, as well as the purposes and usefulness of studying the history of Islamic education. Through this discussion, the journal offers profound insights into the contribution of Islamic education to shaping human civilization. The conclusion drawn from this journal is that understanding the concept of the history of Islamic education has significant implications for shaping worldviews and human behavior. Thus, this study provides a solid foundation for the development of relevant and impactful Islamic education in contemporary contexts.